A second species of the genus Helibatus Mulsant & Rey, 1859 (Coleoptera: Tenebrionidae: Opatrina) - Iwan, Dariusz; Schimrosczyk, David (Zootaxa, 2013)
The genus Helibatus consists of two species: H. morio Mulsant & Rey, 1859 and newly described H. banaszkiewiczae sp. nov. The species differ from each other in the structure of the metaventral process. The genus is distributed inSouthern Africa – a distribution map for the two known species is provided.